Evaluation of the Worldwide Occurrence of Rabies in Dogs and Cats Using a Simple and Homogenous Framework for Quantitative Risk Assessments of Rabies Reintroduction in Disease-Free Areas through Pet Movements - Crozet, Guillaume (Vet Sci, 2020)
Dog and cat rabies cases imported from rabies enzootic countries represent a major threat for areas that have acquired rabies-free status and quantitative risk analyses (QRAs) are developed in order to assess this risk of rabies reintroduction through dog and cat movements. Herein we describe a framework to evaluate dog and cat rabies incidence levels in exporting countries along with the associated uncertainty for such QRAs. For enzootic dog rabies areas (EDRAs), we extended and adapted a previously published method to specify the relationship between dog rabies vaccination coverage and canine rabies incidence; the relationship between dog and cat rabies incidences; and then to predict annual dog and cat rabies incidences. In non-enzootic dog rabies areas (nEDRAs), we provided annual incidence based on declared dog and cat rabies cases. For EDRAs, we predicted an annual incidence potentially greater than 1.5% in dogs and about ten times lower in cats with a high burden in Africa and Asia but much lower in Latin America. In nEDRAs, the occurrence of rabies was lower and of similar magnitude in dogs and cats. However, wildlife could still potentially infect dogs and cats through spillover events. This framework can directly be incorporated in QRAs of rabies reintroduction.